Tuberous Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
A 14-year-old girl with bilateral renal cell carcinoma (hypernephroma) complicating a previously unrecognized tuberous sclerosis is reported from Cornell Univ Med College, NY, and North Shore Univ Hosp, Manhasset, NY, together with a review of 6 similar cases culled from the literature.